Glomus sp. and Bacillus sp. strains mitigate the adverse effects of drought on maize (Zea mays L.) - Wilmowicz, Emilia; Kućko, Agata; Bogati, Kalisa; Wolska, Magdalena; Świdziński, Michał; Burkowska-But, Aleksandra; Walczak, Maciej (Frontiers in Plant Science, 2022)
Maize (Zea mays) is an economically important source of food and feed. This species is highly sensitive to drought, which is the most limiting factor for crop biomass yield. Thus, maize cultivation methods should be improved, especially by environment-friendly agricultural practices, such as microorganisms. Here we provide evidence that Glomus sp. and Bacillus sp. modulate maize response to drought. Inoculation of maize seeds by these microorganisms restored the proper photosynthetic activity of plant under drought and stabilized the leaf osmoprotectant content. The beneficial effect of Glomus sp. and Bacillus sp. was also related to the stabilization of cell redox status reflected by H2O2 content, antioxidant enzymes, and malondialdehyde level in leaves. As we revealed by several methods, shaping maize response to drought is mediated by both microorganisms through modification of cell wall composition and structure in leaves, such as downregulation of pectin, affecting their methylation degree, and increasing hemicelluloses content. Overall, we provide new information about mechanisms of maize drought tolerance induced by Glomus sp. and Bacillus sp., which is a promising approach for mitigating abiotic stresses.